Adsorption characteristics of activated carbons and carbon dioxide systems - Ang, Chek Kuan (2011)
In this project, an experimental apparatus is fabricated to study physical gas adsorption between carbon dioxide and carbonaceous adsorbents, for the purpose of artificial carbon dioxide sequestration. The adsorption process is studied at constant temperature to determine its experimental fit with various isotherm models.